2008
DOI: 10.1063/1.2933523
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Lewis acid sites on the (100) surface of β-AlF3: Ab initio calculations of NH3 adsorption

Abstract: The current study employs hybrid-exchange density functional theory to show that the Lewis base, NH 3 , binds to the β-AlF 3 (100) surface with a binding energy of up to -1.96 eV per molecule. This is characteristic of a strong Lewis acid. The binding of NH 3 to the surface is predominately due to electrostatic interactions. There is only a small charge transfer from the NH 3 molecule to the surface. The binding energy as a function of coverage is computed and used to develop a lattice Monte Carlo model which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 28 publications
3
24
0
Order By: Relevance
“…One way to quantify the Lewis acidity is the adsorption of small molecules like CO and NH 3 , where their lone pairs can bind to the positively charged catalytic centres. The adsorption of carbon monoxide (CO) and ammonia (NH 3 ) as probe molecules is an essential tool in the characterization of a surfaces' local properties [8][9][10][11][12][13][14][15]. Due to their adsorption at the active sites, the corresponding frequency shifts allow an estimation of Lewis-acidities, both experimentally and computationally [8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…One way to quantify the Lewis acidity is the adsorption of small molecules like CO and NH 3 , where their lone pairs can bind to the positively charged catalytic centres. The adsorption of carbon monoxide (CO) and ammonia (NH 3 ) as probe molecules is an essential tool in the characterization of a surfaces' local properties [8][9][10][11][12][13][14][15]. Due to their adsorption at the active sites, the corresponding frequency shifts allow an estimation of Lewis-acidities, both experimentally and computationally [8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Motivated by the outlined diversity in applications of the sol-gel prepared metal fluorides and the versatile path to their synthesis, computational work on these materials started with the investigation of the AlF 3 surface both in the α-and β-modification [45,46]. The emphasis was placed on the modeling of the Lewis-acid sites and the catalytic behavior of the fluoride materials.…”
Section: Introductionmentioning
confidence: 99%
“…A strong Lewis acid can be characterised by a large NH 3 binding energy and a large blue shift in the stretching frequency of adsorbed CO. The reactivities of under-coordinated Al ions on several AlF 3 surfaces have previously been characterised via the calculation of their NH 3 binding energies and CO stretching frequencies 24,26 . While all sites display at least moderate Lewis acidity, the sites displaying the strongest Lewis acidity consist of under-coordinated Al ions bound to five bidentate F ions 24,26 .…”
Section: Introductionmentioning
confidence: 99%
“…It has previously been shown that HCl can dissociate upon adsorption at the surface of β-AlF 3 and that there is either no energy barrier or a very low energy barrier to the dissociation 24 . It is proposed here that CCl 2 F 2 dismutation initially involves dissociation of the molecule upon adsorption.…”
Section: Introductionmentioning
confidence: 99%